1986
DOI: 10.1111/j.1365-2362.1986.tb01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo perfusion of plasma over protein A columns in human mammary adenocarcinoma. Role of the Fc‐binding capacity of protein A in the side effects and the tumoricidal response

Abstract: Plasma of twelve patients presenting with a metastic mammary adenocarcinoma was perfused ex vivo over columns of protein A covalently linked to crystalline silica. The plasma of seven patients (group A) was perfused over columns of protein A exhibiting a normal Fc-binding capacity and the plasma of five (group B) over columns of protein A in which the Fc-binding capacity was destroyed. In group A, all patients experienced acute, easily manageable, side effects (hypotension, chills, mild fever, leucocytosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This protein is a cell wall component of the bacterium Staphylococcus aureus that binds specically to many mammalian immunoglobulins, most markedly IgG and is utilized for oriented immobilization of antibodies from different sources. [36][37][38] Here, Ni 2+ was modied on the surface of MnFe 2 O 4 @ SiO 2 @NH 2 @2AB and the application of these magnetic nanoparticles was investigated in purication of 6Âhistidine-tagged recombinant protein-A from crude E. coli lysate as depicted in Scheme 2. MnFe 2 O 4 @SiO 2 @NH 2 @2AB-Ni magnetic nanoparticles were added to the Soluble Cell Extract (SCE) and the mixture was incubated for 30 min with continuous shaking.…”
Section: Purication Of 6âhis-tagged Proteinsmentioning
confidence: 99%
“…This protein is a cell wall component of the bacterium Staphylococcus aureus that binds specically to many mammalian immunoglobulins, most markedly IgG and is utilized for oriented immobilization of antibodies from different sources. [36][37][38] Here, Ni 2+ was modied on the surface of MnFe 2 O 4 @ SiO 2 @NH 2 @2AB and the application of these magnetic nanoparticles was investigated in purication of 6Âhistidine-tagged recombinant protein-A from crude E. coli lysate as depicted in Scheme 2. MnFe 2 O 4 @SiO 2 @NH 2 @2AB-Ni magnetic nanoparticles were added to the Soluble Cell Extract (SCE) and the mixture was incubated for 30 min with continuous shaking.…”
Section: Purication Of 6âhis-tagged Proteinsmentioning
confidence: 99%
“…The plasma of twelve patients presenting with a breast adenocarcinoma and metastatic lesions was perfused e x vivo over protein A columns of about 100 ml as previously described [2]. The plasma of seven patients (group A) was perfused over columns containing 200 mg of 'native' protein A, i.e., protein A exhibiting a normal Fc-binding activity, and the plasma of five patients (group B) over columns containing 200 mg of 'denatured' protein A, i.e., protein A in which the Fc-binding activity was destroyed by heating protein A for 0.5 h at 110°C (1 mg ml-' of PBS, pH 7.4).…”
Section: Detection Of Protein a During Plasma Perfusion Over Protein mentioning
confidence: 99%
“…Recently, it has been shown [I, 21 that the ex vivo plasma perfusion over columns of protein A, a cell wall component isolated from most strains of Staphylococcus aureus, induces a tumoricidal response in some patients presenting with a breast adenocarcinoma and metastatic lesions. Although the Fc-binding capacity of protein A is most probably responsible for this Correspondence necrolytic response [2], the precise mechanisms involved remain poorly understood. Theoretically, two major hypotheses may be advanced: a 'column effect', i.e., the removal of antigen-antibody complexes from the plasma, leading to the appearance of cytotoxic antibodies in the processed plasma [3], or a 'leaking effect' (or both), i.e., the infusion of some agents stimulating the patients' immune response (protein A?)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinet [5] has shown that the anti-n eoplastic activ ity of S PA colum ns for hum an breast adenocarcinoma is lost when SPA is chemically treated to destroy its ability to bind antibo dy. Das and Langone [21] have shown that the anti-n eoplastic activ ity for system ic SP A therapy in m ice is also dependent on S PA' s IBF activit y.…”
mentioning
confidence: 99%